Comparative study between Malaysian and Nigerian formal low cost housing policy issues - Ubale, Mohammad Yahaya (2013)
The current housing policies of Malaysia and Nigeria do not highlight on the af- fordability of formal low cost houses (FLCH). Low income earners do not have sufficient income to buy food and meet basic necessities like clothing, rent, fuel, utilities, transport, communications, medical expenses, education, and on a broader sense, housing. The objectives of this study were (i) to investigate FLCH afforda- bility elements in the current housing policies of Malaysia and Nigeria; (ii) to com- pare the FLCH affordability elements in Malaysia and Nigeria; (iii) to study the re- lationship among the FLCH affordability elements in Malaysia and Nigeria; and (iv) to accomplish a sustainable FLCH affordability policy for the LIGs. The meth- odologies employed include descriptive statistics, Pearson correlation and the t-test. The study found that there are no laws, rules or guidelines regulating the affairs of FLCH. The design does not reflect user need; it did not conform to their culture, family background and size. No provisions for public participation are provided in the policy documents. FLCH are located in the same neighbourhood with medium and high cost houses in Batu Pahat Malaysia and enjoy all facilities, utilities and services there. The situation is not the same in Bauchi town, where FLCH are lo- cated separately at the peripheries outside of the town trekking distances which re- pel beneficiaries because of the awkward location. Residents in Batu Pahat have higher earnings, less number of dependants than those at Bauchi who have higher number of dependants and lower income level. This study recommends that design, location, participation, highlight on affordability and family issues have prominent impact on affordability and hence be incorporated in policy documents. It can therefore be resolve that FLCH in Batu Pahat, are affordable while those in Bauchi are not affordable. Conclusively, these affordability elements should be upheld to ensure sustainable FLCH affordability policy for the low income groups. The physical and socio-economic elements are the catalyst in the housing provision as- pect. These elements can bridge the wide fissure being the basic features, essentials and the fundamentals of a good policy.